ENSURING THE STABLE OPERATION OF MACHINERY THROUGH THE USE OF MAINTENANCE LUBRICANTS - Abutolib Sobirjonov; Vaxob Meliev; Ilxomjon Usmanov; Shuxrat Alimov (Web of Journals Publishing, 2024)
In recent years, the agriculture of Uzbekistan has relied on the complete mechanization of sowing, cultivation and harvesting operations. Expensive imported equipment is purchased. And how is this technique used, how is it stored, how many years will it serve the farmers? Previously, it was practiced to write off equipment after 6-7 years of being on the farm. At the present time, the technology cannot pay for itself during this period. One of the reasons is the susceptibility of technology to corrosion. This article discusses the causes and consequences of corrosion, suggests ways to extend their service life.
Keywords: corrosion, engineering, chain transmission, preservation, corrosion inhibitor, lubricants, wear.